Dental Laboratory Production of Prosthetic Restorations in a Population in Sofia, Bulgaria: A Descriptive Study - Nikola D. Damyanov; Dick J. Witter; Anneloes E. Gerritsen; Nico H. J. Creugers (International Journal of Dentistry)
Objective. To describe prosthodontic production related to mutilated dentitions in Sofia, Bulgaria. Methods. Prosthodontic production from 5 dental laboratories was recorded during a 14-day period. Production was related to dentitions as noted from casts. Dentitions were classified as edentulous, interrupted/reduced, slightly interrupted, shortened, and complete. The representativeness of the laboratory sample was verified trough comparison with a Sofia population sample using proportions of crowned or replaced teeth per dental region. Results. The total production consisted of 243 crowns, 16 post and cores, 82 fixed dental prostheses, and 41 removable dentures. Proportions of crowned teeth were significantly different between the samples; proportions of replaced teeth were not. Of the 58 incomplete dentitions analyzed, 19 were restored to the level of completeness, 15 resulted in slightly interrupted, and 24 in shortened dentitions. Conclusions. Predominantly fixed restorations were provided to restore mutilated dentitions to a functional level and not necessarily to complete dentitions.